Performance Studies Of IEEE 802.11 AC Laboratory Links - Carvalho, José Pacheco De (2022)
Wireless communications, involving electronic devices, have been increasingly important in society. Performance is a fundamental issue, resulting in more reliable and efficient communications. Security is also essential. Laboratory measurements are presented about several performance aspects of Wi-Fi IEEE 802.11ac WPA2 point-to-point links. Our study contributes to performance evaluation of this technology under WPA2 encryption, using new available equipments (Cisco 2702i access points and Edimax USB 3.0 AC 1200 adapters adapters). New results are given from TCP and UDP experiments concerning TCP throughput versus TCP packet size, jitter and percentage datagram loss versus UDP datagram size. Comparisons are made to results obtained for other IEEE 802.11 technologies. Conclusions are drawn about the comparative performance of the links.